Pengaruh Keadilan Distributif dan Keadilan Prosedural Terhadap Keefektifan Partisipasi Penyusunan Anggaran dalam Meningkatkan Kinerja Pimpinan SOPD - Dewi Lesmanawati; Mellani Yuliastina (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2020)
The present research examined the effects that participation in budget preparation had on performances of Offices in Palangka Raya City. The offices turned to be executive elements of Local Government directly involved in budget preparation and served as working unit providing public services. Distributive justice and procedural justice were treated as moderating variables of the research. Samples taken in the research involved offices in Palangka Raya city. Analysis units utilized were the heads of offices, since they were mostly involved in budget processing in the offices. Data were collected through questionnaires and interviews. Out of 82 questionnaires sent, only 48 questionnaires could be processed. Instrument analysis manipulated to process data was regression method with residual approach.The empirical result using simple regression show that budget participation influence on performance. But empirically result using residual approach show that a fit between budget participation with contingent factor (distributive justice and procedural justice) does not effect performance significantly. Keywords: budget participation, performance, distributive justice and procedural justice